Steinernema tophus sp. n. (Nematoda: Steinernematidae), a new entomopathogenic nematode from South Africa - Çimen, Harun; Lee, Ming-Min; Hatting, Justin; Hazir, Selcuk; Stock, S. Patricia (Zootaxa, 2014)
A new entomopathogenic nematode, Steinernema tophus n. sp. is described from South Africa. Morphological, molecular (ribosomal gene sequence data) together with cross-hybridization studies were used for diagnostics and identification purposes. Both molecular and morphological data indicate the new species belongs to the ‘glaseri-group’ of Steinernema spp. Key morphological diagnostic traits for S. tophus n. sp. include the morphology of the spicules and gubernaculum. Morphometric traits of third-stage infective juveniles, including total body length (average 1,046µm), tail length (average 70µm), location of the excretory pore (average 92 µm), D% (average 63), E% (average 132) and H% (average 32) values are definitive. In addition to these morphological characters, analysis of rDNA (28S and ITS) gene sequences depict this Steinernema species as a distinct and unique entity.